Process piping design handbook. Volume one, - Smith, Peter, 1951 June 7- (Gulf Pub., 2007)
Written for the piping engineer and designer in the field, this two-part series fills a void in piping literature, since the Rip Weaver books of the '90s were taken out of print at the advent of the Computer Aid Design (CAD) era. Technology may have changed, however the fundamentals of piping rules still apply in the digital representation of process piping systems. The Fundamentals of Piping Design is an introduction to the design of piping systems, various processes and the layout of pipe work connecting the major items of equipment for the new hire, the engineering student and the veteran engineer needing a reference.
Keywords: Pipelines -- Design and construction.; Piping -- Design and construction.; Piping -- Computer-aided design.; Petroleum refineries -- Equipment and supplies.; elektronické knihy; electronic books